The work of rails under conditions of various average static axial loads of rolling stock - M. I. Titarenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
The analysis of failure of unhardened and heat-strengthened R65 rails under operating conditions in the tangent sections of the track is presented taking into account the influence of the most important operational factor - the average static axial loads of the rolling stock. Non-reinforced R65 rails in the jointed track on the 12.5 m long wooden sub-rail base were considered based on the results of their single replacement in the entire range of their failures. The work of rails under operating conditions is estimated at average static axial loads of rolling stock as 7.5, 9.5, 16.5 and 19.5 tf (73.55, 93.16, 161.82 and 191.21 kN) at all stages of the tonnage at each load. The influence of the average static axial loads of the rolling stock on rail failure in specific operating conditions has been revealed. The features of the change in the intensity of rail failure are considered at all stages of their operation, both for the specified and for the average network level of the static load. The obtained statistical data on the effect of axial loads of rolling stock on the operation of rails can be used in the practice of track maintenance. In conditions of increasing axial loads up to 25, 27 tf, it is necessary to use rails of the appropriate quality; also it is expedient to create new rails for such operating conditions. It is necessary to perform an evaluation of the real operational qualities of the rails in order to use the rolling stock with the increased axial loads (25, 27 tf) in the transportation process in the most efficient way. In the long term, the results of such studies will be aimed at improving the operation of the systems for running track and railway car complexes.